(untitled) (Third Sector Social Economic Review, 2022)
It is known that in today’s competitive market conditions, employees, society, customers and shareholders, known as stakeholders, have a significant impact on companies to continue their activities and maximize their profits. Especially with the changing world order, companies need to be in a respectable and reputable position in the eyes of stakeholders as well as make profits. Therefore, it is stated that companies must comply with ethical values both to display an effective and productive appearance in the market and to affect their organizational performance positively. Thus, it is foreseen that they will gain a stronger position in the market by providing legitimacy in the eyes of the stakeholders. Within the scope of our study, it is aimed to explain the effect of ethical leadership perception on the organizational commitment of academicians and to reveal whether the concept of ethical climate has a mediating effect on the specified variables. In this context, academic staff working at foundation universities within the provincial borders of Istanbul were included in the evaluation. For sampling, by the result of the correlation and regression analyses of 411 academicians’ surveys made by utilizing the SPSS 25.0 program package, it was observed that ethical leadership positively affected the ethical climate. In addition, it was determined that ethical leadership and ethical climate perceptions positively affect emotional commitment, continuance commitment and normative commitment, which are expressed as sub-dimensions of organizational commitment. On the other hand, another conclusion shown by the analysis is that the ethical climate has a mediating effect between ethical leadership and organizational commitment variables.